Advanced surface modification techniques for titanium implants: a review of osteogenic and antibacterial strategies - Zhang, Handong; Wu, Zidong; Wang, Zemin; Yan, Xinfeng; Duan, Xudong; Sun, Huaqiang (Frontiers in Bioengineering and Biotechnology, 2025)
Titanium (Ti) implants are widely used in orthopedic and dental applications due to their excellent mechanical strength, corrosion resistance, and biocompatibility. However, their limited osteointegration and susceptibility to bacterial infections remain major clinical challenges. Recent advancements in surface modification techniques have significantly improved the osteogenic and antibacterial properties of Ti implants. This review summarizes key strategies, including ion doping, hydroxyapatite (HAp) coatings, nanostructured surfaces, and graphene-based modifications. Zinc (Zn)-doped coatings increase osteoblast proliferation by 25%, enhance cell adhesion by 40%, and inhibit Staphylococcus aureus by 24%. Magnesium (Mg)-doped Ti surfaces enhance osteoblast differentiation, with 38% increased alkaline phosphatase (ALP) activity and a 4.5-fold increase in cell proliferation. Copper (Cu)-doped coatings achieve 99.45% antibacterial efficacy against S. aureus and 98.65% against Escherichia coli (E. coli). Zn-substituted HAp promotes mineralized nodule formation by 4.5-fold and exhibits 16.25% bacterial inhibition against E. coli. Graphene-based coatings stimulate bone marrow stem cells (BMSCs) and provide light-responsive surface potentials for enhanced osteogenesis. Despite these advancements, challenges remain in optimizing ion release kinetics and long-term stability. Future research should focus on multi-functional coatings that integrate osteogenic, antibacterial, and immunomodulatory properties to enhance clinical performance and patient outcomes.